A Review Of The Literature Of Quality And Performance Management - Reynold Pieter Jordan Vigeleyn Nikijuluw (JURNAL MANEKSI, 2017)
The meaning of quality and performance are different, however, they related in terms of management activity. In management, the existence of the two activities is unavoidable. Therefore, given the boundaries of success and failure is very thin. For these reason in-depth examination these terms and their relationship. In this paper we are going to discuss; strategic human resource management, the definition of quality and performance management, the History of Quality Management, Why quality and performance management, the purpose of quality and performance management, Quality and performance management principles, and performance appraisal.Quality, "Customer satisfaction" is the main element when defining and describing quality. If the ability to maintain the existing customer base, as well as obtain new customers, then the quality is achieved. Enthusiasts for performance assessment argue that it serves a key integrating role within an organization's human resource processes. Firstly, it provides a checking mechanism for resourcing policies and procedures, evaluating the quality of recruits and hence the underlying decision-making process. Secondly, it monitors employee commitment and the relevance of their working behaviour to business objectives. Thirdly, it provides a rationale for an organization's pay policies. Taken at face value, these intentions seem entirely compatible with an integrated and strategic approach to human resource management. In reality, however, the definition and measurement of good performance is a controversial matter, involving fundamental issues of motivation, assessment and reward.